Аналіз впливу матеріальних витрат на формування собівартості продукції, робіт або послуг підприємства - Роєва, О. С.; Роева, О. С.; Roieva, O. (ЦНТУ, 2018)
У статті проведено аналіз матеріальних витрат підприємств водопровідно-каналізаційного господарства з метою виявлення можливості раціонально використання матеріальних ресурсів та розробки заходів щодо виявлених резервів. Виходячи зі специфіки діяльності підприємств, що надають послуги з водопостачання та водовідведення, визначено об’єкт та предмет дослідження. Запропоновано впровадження низки організаційно-технічних заходів, що дозволять досягти оптимізації рівня витрат та зниження ціни одиниці продукції. В статье проведен анализ материальных затрат предприятий водопроводно-канализационного хозяйства с целью выявления возможности рационально использования производственных ресурсов и разработки мероприятий по выявленным резервам. Определены объект и предмет исследования, исходя из специфики деятельности предприятий, предоставляющих услуги водоснабжения и водоотведения. Предложено внедрение ряда организационно-технических мероприятий, которые позволят достичь оптимизации уровня затрат и снижения цены единицы продукции. The goal of this research is to identify the opportunities for cost reduction, rational and efficient use of production resources and decrease in the unit price of the services provided by the water and sewage enterprises. Analysis of the costs of the services provided by the water and sewage enterprises aims to identify the possibility of rational use of production resources, information support and comprehensive assessment of cost optimization results was achieved. The expenditure level for water supply and sewerage as well as the effectiveness of the recourses application in the industry forms the index of cost price. Net cost of the works or services produced or provided by water and sewage enterprises includes all costs of drinking water extraction, production and supply to the consumers, water collection, drainage and purification for further use or release into the water ponds (including hot water and water purified in the municipal buildings). Net cost is calculated by type of production process (water lifting, supply to water network, treatment and supply to the consumers) and type of services - water supply and sewage. Water and sewage enterprises, in addition to standard costing items, introduce Purchase Water item. These item costs are included in the net cost of work at the production cost of water. Thus, service net cost analysis is an important cost management tool that enables generalized evaluation of the effectiveness of the production resources and discovering the reserves to increase the enterprise’s profitability and reduce service unit price. The results of the research were leading us to the following conclusions. As well as the reserves of spending cuts are set for each costing item, therefore by eliminating unnecessary cost overruns and unproductive ones in overhead costs, such as savings of lubricants, lighting, reserves of service cost reduction is energy savings through the implementation of organizational and technical measures in compliance with the production process. Also, the replacement of existing tariffs for water supply and sewerage in favor for new economically justified ones that are appropriate in the current economic conditions, management of water supply and sanitation leads to reduction of costs associated with providing operating company, profits and improve competitive ability of enterprises to future.
Анализ влияния материальных затрат на формирования себестоимости продукции, работ или услуг предприятия
Analysis of the Influence of Material Cost on the Formation of the Cost of Production, Works or Services of the Enterprise
Keywords: аналіз; матеріальні витрати; водопровідно-каналізаційні господарства; собівартість; загально виробничі витрати; анализ; производственные затраты; водопроводно-канализационные хозяйства; себестоимость; общепроизводственные расходы; analysis; material expenses; water supply – sewage farms; prime cost; total expenditures